Análise temporal de dados de monitoramento de colmeias de abelhas - Trindade, Nilton Cardoso (2018)
This study proposes a new perspective for the beekeeping management, thru time series analysis of monitoring data of beehives. Starting from the analysis of the current management on beekeeping and its importance for development and sustainability of the agricultural world model of fruit growing in the face of the almost umbilical need of both. The new view of digital beekeeping management is based on data collection based on sensors, whose data are transmitted by satellite and stored in a cloud that allows beekeepers access to the conditions existing inside and outside the hives. It`s allow the beekeeper a management based in the received information about the humidity and internal and external temperature of the beehive, as well the direction and speed of wind, besides rainfall and mainly the mass of the hives by time elapsed. This information allows the beekeeper to know the exact moment of doing some intervention in the hive, knowing in advance and not by speculation the need for each beekeeping management. All these data will allow following the behavior of the Colonies, which may contribute to the study of one of the most serious current problems that is the Colony Collapse Disorder.